Identification of Training Models to Improve Lower Limb Muscle Strength during Volleyball Spike Movement - Nurul R, Sabila; Budiman, Ali; Sulistiadinata, Heru (STKIP Paasundan Press, 2025)
Volleyball has been known in Indonesia since 1928, introduced by Dutch teachers in secondary schools. It later developed nationally with the establishment of the Indonesian Volleyball Association (PBVSI) on January 22, 1955, in Jakarta. The objective of this study is to identify effective types of training models to strengthen lower limb muscles in order to support optimal performance during spike movements, through an in-depth analysis of relevant and evidence-based literature. This research employs a Systematic Literature Review (SLR) approach. Data were collected from several databases such as Google Scholar, JPJO, Taylor and Francis, and DOAJ, with publication years ranging from 2015 to 2024. After applying inclusion and exclusion criteria, a total of 10 relevant articles were selected and analyzed thoroughly. The results show that **plyometric training models** are highly effective in increasing explosive power and vertical jump height—both of which are key factors in successful spike execution. Exercises such as depth jumps, tuck jumps, and bounding stimulate the neuromuscular system to produce rapid force output.